Immobilization of Catalase Using PAES-C Polymer for Wastewater Biological Treatment Research. Issue 1 (February 2021) - Bi, Haiyan; Tian, Jiaying; Fu, Ye; Wang, Dazhi; Cai, Weijie
Abstract: PAES-C polymer modified by glutaraldehyde (GA) was selected to immobilize the catalase. Infrared spectrum analysis and 1 H NMR test the presence of - COOH bond in PAES-C, which favored the cross-linking of PAES-C with catalase. The SEM image showed that its surface had a porous structure, which increased its surface area and provided more active sites for the immobilization of catalase. Indeed, the influence of various factors including GA mass concentration, modification time of GA and carrier, cross-linking time of modified carrier and catalase on the immobilization capacity were deeply investigated. In particular, the achieved optimal conditions for immobilization of catalase were as following: GA mass concentration was set at 1.0wt%, GA modification time was 1.0 h, and the binding time between the modified carrier and the enzyme was 1.0 h. Herein, the findings in this work revealed that PAES-C polymer might be one of the promising candidates for wastewater biological treatment and immobilization of other enzyme.